Nurses’ Attitudes Toward End-of-Life Care: A Cross-Sectional Study - Mohamed, Nurul Azlinda; Ibrahim, Amirah Fatin; Baharudin, Ayuni Asma’; Atarhim, Mohd Arif (Proceedings Series on Health & Medical Sciences, 2025)
End-of-life care is an important aspect of holistic nursing care. As a frontliner, nurses play a significant role in end-of-life care delivery and their attitudes influence the quality of care provided to end-of-life patients and families. This study aims to assess nurses’ attitudes toward end-of-life care and examine the relationship between demographic characteristics with nurses’ attitudes. A descriptive cross-sectional study was conducted among registered nurses at a public hospital in Malaysia. Using a simple random sampling, 223 nurses were recruited. Data were collected via an online form using the Frommelt Attitudes Toward Care of The Dying Scale (FATCOD). Descriptive statistics were used to assess demographic characteristics and attitude scores, meanwhile independent t-tests was used to examine group differences. Majority of nurses (89.24%) had a fair attitude, 7.62% showed a positive attitude and 3.14% had negative attitude. Among the six subscales, “Family as Caring” subscale recorded the highest mean score (M = 4.39, SD = 0.65), followed by “The Care of the Family” subscale (M = 4.12, SD = 0.69). Meanwhile the lower scores were observed in “Communication” subscale (M = 3.13, SD = 0.49) and “Fear/Malaise” subscale (M = 3.29, SD = 0.59). A statistically significant difference was found between years of working experience with total attitude scores (p = 0.04). Nurses demonstrated positive attitudes toward family-related care for end-of-life patients. However, emotional and communication challenges may compromise holistic care. Educational effort should prioritize communication skills and emotional resilience to enhance compassionate end-of-life care for patients and families.